Overview Of Regency and City Regional Tax Calculations at Bappenda Gowa Regency - Andi Rustam; Warda Warda; Nurul Azizah (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the calculation of local taxes at the Gowa Regency Bapenda office. The technique in this study uses applied qualitative techniques. The research data was obtained by the author through interviews, observations and documentation from the research site. The results showed that the calculation of district and city taxes was very effective, judging from its development from an average value of 3 years, namely from 2019- 2021 the percentage of the results was 114.05% although the results were very effective, basically there were still some obstacles experienced by the Gowa Regency Bapenda. namely the lack of knowledge and public awareness related to tax obligations, There are still taxpayers who do not understand the importance of paying taxes and the benefits that will be felt by taxpayers directly by paying taxes. In addition, the lack of awareness and compliance of registered taxpayers in paying their tax obligations in accordance with applicable regulations.